The philosophy of the mask in the poetry book by B. Pasternak “Themes and variations” - Markov Alexander Viktorovich; Shtayn Oksana Aleksandrovna (Studia Humanitatis)
The article examines the function of the mask in Boris Pasternak’s poetry as a semiotic construct combining protective and expressive roles. In Pasternak’s works the mask does not conceal but reveals the true self becoming a form of existential honesty amid historical crisis. The analysis explores the connection between masking, corporeality, illness and the political context of the 1920s. Pasternak’s mask is interpreted as a strategy of resistance to discourses through irony and theatricality. The study shows how the poet redefines traditional notions of the mask, making it a central element of his poetics.